Wage Distribution in the Period of Economic Growth with Income Distribution: The Case of Brazil - Baltar, Carolina Troncoso (Panoeconomicus, 2020)
This paper analyses in detail the distribution of Brazilian wages in the period of economic growth with income distribution. Brazil presents a high structural heterogeneity that generates high wage inequality, and it is shown that wage differences within occupational categories are greater than wage differences between occupational categories. Higher GDP growth followed by an incomes policy that raised low wages reduced wage differences especially within occupational categories rather than wage differences between occupational categories. Key words: Income distribution, Wage distribution, Employment. JEL: E24, O15.